Fostering rapid transitions to education for sustainable development through a whole-system approach to curriculum and organizational change - Desha, C.; Hargroves, Charlie (Peter Lang Pub Incorporated, 2012)
This book, prepared in the context of the Conference on Sustainable Development, also known as Rio+20, contains the papers submitted to the World Symposium on Sustainable Development at Universities (wssd-u-2012).